PRACTICE OF DEVELOPMENT OF STUDENTS’ ADDITIONAL INTERDISCIPLINARY COMPETENCIES IN A MODERN UNIVERSITY - E. G. Syryamkina; T. B. Rumyantseva; E. Yu. Liventsova (Образование и наука)
The aim of the article is to show the possibilities of formation ofnew approaches to the development of additional interdisciplinary competencies of university youth in modern conditions.Methods. The methods involve such theoretical methods as analysis of scientific literature and documents, generalization of empirical data.Results and scientific novelty. The article includes experience of many years in the sphere of development of students’ additional interdisciplinary competencies of the National Research Tomsk State University (TSU). The authors present cases of two TSU structural subdivisions: Center for Social and Professional Volunteering and Park of Social and Humanitarian Technologies. The effective educational technologies proposed by the authors are analysed. Transition from the theoretical (knowledge) training of students to practically-oriented training is an actual trend today. A graduate of a modern university should have a broad vision, communication skills, desire for cooperation, self-development, creative application of gained knowledge and lifelong learning, in other words –the development of students’ additional interdisciplinary competencies. In this regard, the role of students’ extracurricular practical work in a university is increasing. This work requires organizational and educational support. The article gives description and analysis of effective educational forms of technologies for development of students’ additional interdisciplinary competencies within their extracurricular activities in the mentioned above structural units of the university.Practical significance. Higher educational establishments can use presented materials for improvement of an educational process.